THE HISTORICAL AND ARCHAEOLOGICAL HERITAGE OF THE UZHANSKA VALLEY AS A FACTOR IN THE DEVELOPMENT OF COGNITIVE TOURISM IN UZHHOROD DISTRICT - Kochan, Vasyl (SWorld-Ger Conference proceedings, 2024)
The article deals with the historical and archaeological resources of the Uzhanska Valley as a historical and geographical region of Uzhhorod district, which could become a potential tourist product for the development of cultural and educational tourism.